2014
DOI: 10.1098/rspb.2013.2680
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the appearance of a badge of status causes changes in true badge expression

Abstract: Signals of dominance and fighting ability (i.e. status signals) are found in a wide range of taxa and are used to settle disputes between competitive rivals. Most previous research has considered status-signal phenotype as an attribute of the individual; however, it is more likely that signal expression is an emergent property that also incorporates aspects of the social environment. Furthermore, because an individual's signal phenotype is likely to influence its social interactions, the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 45 publications
3
64
0
Order By: Relevance
“…Despite clear evidence that females display condition dependence in bare parts (Gladbach et al 2010, Kelly et al 2012, Rosenthal et al 2012, Doutrelant et al 2013 and use them for signaling (Nolan et al 2010, Dey et al 2014, Tarvin et al 2016, there has been little study of female bare parts in relation to those of males. Females experience intrasexual competition largely for high-quality mates (Rosvall 2011), and their bare parts can play an important role in competitive interactions (Murphy et al 2009) and male mate choice (Torres and Velando 2005, Cornwallis and Birkhead 2007a.…”
Section: The Importance Of Avian Bare Parts As Signalsmentioning
confidence: 99%
“…Despite clear evidence that females display condition dependence in bare parts (Gladbach et al 2010, Kelly et al 2012, Rosenthal et al 2012, Doutrelant et al 2013 and use them for signaling (Nolan et al 2010, Dey et al 2014, Tarvin et al 2016, there has been little study of female bare parts in relation to those of males. Females experience intrasexual competition largely for high-quality mates (Rosvall 2011), and their bare parts can play an important role in competitive interactions (Murphy et al 2009) and male mate choice (Torres and Velando 2005, Cornwallis and Birkhead 2007a.…”
Section: The Importance Of Avian Bare Parts As Signalsmentioning
confidence: 99%
“…Mougeot et al, 2009). In the purple swamphen, shield size (determined by culmen length and shield width) is likely to be sexually determined and can be modified according to social status or season (Craig et al, 1980;Dey et al, 2014). The observed age differences in size suggest that the immatures can still grow slightly until they reach the adult size, as evidenced by some of the study characters in the sample of birds captured as immatures and recaptured as adults (see table S3).…”
Section: Sexual Dimorphismmentioning
confidence: 92%
“…however, this relationship was not met for culmen and shield width, which were bigger for adult females than immature males. These two characters are indicative of shield surface area, and the size of this ornament probably reflects reproductive and/or social status in P. p. melanotus (Craig et al, 1980;Dey et al, 2012Dey et al, , 2014. Shield size is testosterone-dependent in several species of the family Rallidae (Gullion, 1951;Eens et al, 2000) and may function as an indicator of individual quality, as found for many testosterone-dependent traits in birds (e.g.…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…Recently, several empirical studies and reviews have highlighted the importance of social feedback from potential mates and conspecifics about ornament quality on the physiology or behaviour of signallers (e.g., Safran et al, 2008;Rubenstein and Hauber, 2008;Vitousek et al, 2013;Dey et al, 2014;Vitousek et al, 2014b). hormonal data to support such a mechanism, female barn swallows with elevated levels of corticosterone prior to incubation were more likely to abandon their nesting attempt (Vitousek et al, 2014a) and experimentally elevating corticosterone of female tree swallows resulted in lower nestling survival (Ouyang et al, 2015).…”
Section: Chapter 7: Synthesismentioning
confidence: 98%
“…Recently, it also has been suggested that social and physiological costs may act in concert to maintain signal honesty (Tibbetts, 2014;Vitousek et al, 2014b). For example, painting the shield of male pukekos (Porphyrio porphyrio) to reduce the quality of signal displayed resulted in increased aggression from conspecifics and a dynamic reduction in the natural size of the shield following manipulation compared to controls (Dey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%